Enzyme-linked immunosorbent assay for detection of streptolysin O antibodies. - Reitano, M (1986)
An enzyme-linked immumosorbent assay (ELISA), based upon the detection of streptolysin O antibodies in human sera, was developed. Disposable polystyrene tubes, sensitized with streptolysin O antigen, were used as the test vehicles. Corresponding antibodies, present in test sera, were detected by binding of the antibodies to goat anti-human immunoglobulin G conjugated to horseradish peroxidase. Demonstration of bound conjugate was accomplished by monitoring peroxidase activity spectrophotometrically at 450 nm, using 5-aminosalicylic acid as the indicator. A total of 97 human sera, previously analyzed by means of the anti-streptolysin O titration technique, were evaluated with the ELISA procedure. A direct quantitative relationship, found to be statistically significant, was demonstrated between Todd units and absorbance values obtained with ELISA.